Restorative justice, Akuntabilitas, dan Standar Hak Asasi Manusia Internasional dalam Kasus Tindak Pidana Berat oleh Anak di Indonesia - Ardiananta, Elvania Rachmasya Ratu (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
Cases of serious crimes committed by minors, such as murder and sexual violence, have become a significant concern in Indonesia, particularly regarding the perception that the legal system is too lenient toward juvenile offenders. Data indicates a steady increase in juvenile crimes over the past decade, prompting public demands for a more stringent legal approach. This paper analyzes how the Indonesian legal system implements the concept of Restorative justice in handling serious crimes committed by minors, considering the balance between offender rehabilitation and legal accountability that fulfills the victim’s right to justice. Through case studies, legal analysis, and exploration of international standards, this paper evaluates the extent to which Indonesia’s juvenile justice policies align with international human rights principles. Additionally, it examines Indonesia’s role and contributions in shaping global standards on child protection and juvenile criminal justice reform, particularly in addressing serious offenses involving minors